Advanced Rheological Characterization of Asphalt Binders Modified with Eco-Friendly and Polymer-Based Additives Under Dynamic Loading - Ali Almusawi; Shvan Tahir Nasraldeen Nasraldeen (Applied Sciences)
This study explores the rheological performance of bitumen modified with a synthetic polymer (styrene–butadiene–styrene, SBS) and two environmentally sustainable additives—animal bone ash (AB) and waste cooking oil (WCO)—to enhance durability and deformation resistance under dynamic loading. Frequency sweep and linear amplitude sweep (LAS) tests were conducted to evaluate viscoelastic and fatigue behavior. SBS at 5% showed the highest elasticity and fatigue life, making it optimal for heavily trafficked pavements. Among bio-waste additives, 6% AB provided the highest stiffness and rutting resistance in laboratory tests; however, 5% AB offered a better balance between structural integrity and cracking resistance, making it more suitable for general pavement applications. WCO-modified binders demonstrated improved flexibility, with 4% WCO achieving the best balance between elasticity and softening, ideal for low-load or temperate environments. These results highlight the potential of combining synthetic and bio-based waste materials to tailor bitumen properties for sustainable and climate-responsive pavement design.